Multi-layer analysis of quantitative 7 T magnetic resonance imaging in the cortex of multiple sclerosis patients reveals pathology associated with disability. (November 2021) - Lema Dopico, Alfonso; Choi, Seongjin; Hua, Jun; Li, Xu; Harrison, Daniel M
Background: Cortical demyelination is a relevant aspect of tissue damage in multiple sclerosis (MS). Microstructural changes may affect each layer in the cortex differently. Objectives: To evaluate the sensitivity of quantitative magnetic resonance imaging (qMRI) measurements on cortical layers as clinically accessible biomarkers of grey matter (GM) pathology. Methods: Forty-five participants with MS underwent 7 T magnetic resonance imaging (MRI) of the brain. Magnetization prepared two rapid acquisition gradient echoes (MP2RAGE) was processed for T1 -weighted images and a T1 map. Multi-echo gradient echo images were processed for quantitative susceptibility and R2 * maps. Cortical GM volumes were segmented into four cortical layers, and relaxometry metrics were calculated within and between these layers. Results: Significant correlations were found for disability scales and multi-layer metrics, for example, Expanded Disability Status Scale (EDSS) and peak height (PH) in the subpial (T1 : ρ = −0.372, p  < 0.050) and inner (R2 *: ρ = −0.359, p  < 0.050) cortical layers. Multivariate regression showed interdependency between atrophy and cortical metrics in some instances, but an independent relationship between cortical metrics and disability in others. Conclusion: Cortical layer 7 T qMRI analyses reveal layer-specific relationships with disability in MS and allow emergence of clinically relevant associations that are hidden when analysing the full cortex.